Internal and External Assessment Analysis of Math, English and Local Curriculum (Journal of Musikot Campus, 2025)
This study aims to analyze the achievement of grade eight students in community schools within Musikot Municipality according to the type of assessment (internal and external) based on the grades obtained in the final examination. The study uses a descriptive and comparative research design. The data collection is based on the results of the final examination of grade eight students held in the 2081 academic session, which includes English, Mathematics and the local curriculum 'Musikot Serofero'. The data has been pre-processed in MS Excel and analyzed using SPSS 25 software. A high proportion of A+ and A grades is seen in internal assessment, while C and D grades are more visible in external assessment, which is an indicator of grade inflation. Thematic analysis shows that the poor performance of students in Mathematics is evident in external assessment, while weaknesses in writing and comprehension are also seen in English. Although the overall performance in the local curriculum is positive, there is a need for improvement in the depth of the subject. The study provides practical recommendations for policymaking in education by highlighting the fairness, reliability and need for improvement of the assessment system.